STUDI MINAT MEREFERENSIKAN DALAM JASA TRAVEL UMROH - Faza, Hilman; Widiyanto, Ibnu (Diponegoro Journal of Management, 2016)
Travelling is now a secondary need or even a primay need due to the increasing economic welfare of society. As a result, there are a lot of travel packages both domestic and international destination offered by travel agents and low-cost airplane. Hajj and Umroh travel package is one of many package that has a significant increase. A large number of muslim population make travel agents compete to offer their services. PT Farfaza Astatama is one of many travel agents that offers Hajj and Umrah travel package. This study aims to determine whether the core and peripheral quality service affect the customers satisfaction resulting in the customers referral intention in PT Farfaza Astatama.Total of sample used on this research were 400 respondents. The respondents are those who ever used the service of PT Farfaza astatama. The questionnaires were distributed from June 2015 to August 2015. Data collected from the questionnaires was then processed using multiple regression method.The results showed that the variable quality of core services and service quality peripherals positive and significant effect on the variable satisfaction. Variable service quality peripherals greatest impact on satisfaction variable and indirect influence on the referral intention, followed by the variable quality of the core service and satisfaction.